Isolasi dan Identifikasi Bakteri yang Terdapat pada Saluran Pencernaan Ikan Gurami (Osphronemus gouramy) dengan Pemberian Pakan Komersil yang Berbeda [Isolation And Identification Of Bacterial In The Digestive Organ Of Gurami Fish (Osphronemus gouramy) With Different Commercial Feed] - Sri Subekti; Franch Dalahi; Agustono Agustono (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Based on the food habits, gurami is omnivorous fish that feed herbivorous carp tend consists of natural food and artificial feed (pellets). The feed is needed to support the growth and survival of Gurami. If feed is given in accordance with the eating habits of Gurami and contain high nutritional Gurami can then growth accelerated faster. Some types of bacteria found in the digestive tract of animals has an important role in order to improve feed utilization, fish health, and environmental quality improvement and microorganisms. In addition, some bacterial flora in the gastrointestinal tract plays an important role and produce several types of enzymes in the digestive tract may contribute to the metabolism of the host. The purpose of this study was to determine the bacteria in the digestive tract of Gurami (Osphronemus gouramy) were given three different types of commercial feed. This study begins with a sampling of Gurami (Oshpronemus gouramy) of maintenance in the Faculty of Fisheries and Marine at Airlangga University in Surabaya and then do stage isolation and identification of bacteria in laboratory bacteria and Microbiology, Faculty of Veterinary Medicine, Airlangga University Surabaya. This study was conducted in July 2013. This research is a descriptive study, the method of solving the problem by describing the subject matter into a form that is easy to understand and based on facts. Results of research on gurami fish that given by three different types of commercial feed, there are two types of bacteria that dominate in the digestive tract of carp, the Pseudomonas sp. and Serratia sp. Both types of bacteria has the potential to help the digestive system of gurami fish. The result of this research are need for further research using the bacterium Pseudomonas sp. and Serratia sp. as probiotics.